2015
DOI: 10.1186/s12711-015-0136-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of birth-rearing type on weaning weights in meat sheep are systematically associated with differences in mean performance among flocks

Abstract: BackgroundAdjustment of body weights for systematic environmental effects such as dam age and litter size is essential for accurate prediction of breeding values in meat sheep and often accomplished by pre-adjusting records using simple multiplicative adjustment factors, which are derived as ratios of least-squares means of weights of lambs in target and reference classes. However, increasing use of multibreed genetic evaluations that incorporate data from both purebred and commercial flocks has generated conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Progeny of yearling Katahdin ewes had BWT that were 22% less than BWT of progeny of 4-through 7-yr-old ewes whereas BWT for progeny of Polypay yearling ewes were 25% less than BWT of progeny of 4-through 7-yr-old ewes (Notter et al, 2005). However, Notter and Brown (2015) reported that BWT for single and twin lambs by yearling Suffolk ewes were only 19% less than those of progeny of 3-through 6-yr-old ewes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Progeny of yearling Katahdin ewes had BWT that were 22% less than BWT of progeny of 4-through 7-yr-old ewes whereas BWT for progeny of Polypay yearling ewes were 25% less than BWT of progeny of 4-through 7-yr-old ewes (Notter et al, 2005). However, Notter and Brown (2015) reported that BWT for single and twin lambs by yearling Suffolk ewes were only 19% less than those of progeny of 3-through 6-yr-old ewes.…”
Section: Discussionmentioning
confidence: 94%
“…The 11% difference in BWT between single and twin lambs was similar to that observed in NSIP Polypay lambs by Notter et al (2005), but average BWT for triplet and quadruplet Polypay lambs were 18 and 34% less, respectively, than those of twin lambs. Notter and Brown (2015) reported that BWT of twin Suffolk lambs born in NSIP flocks averaged 18% less than those of single lambs and 18% more than those of triplet lambs. Variation in BWT across litter size classes was therefore less for Katahdin lambs than for Suffolk and Polypay lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration for fitting an extra interaction is that there should be enough observations in each subclass to be able to fit it. Otherwise, the estimate will be affected by sampling errors (Notter and Brown 2015). In the data used by this study, there were enough observations in each flock or flock by sex by age subclass to estimate the interactions effect well.…”
Section: Correlation Of Ebvsmentioning
confidence: 99%
“…Thus, proper recording of both birth and rearing type of the lamb, as well as the respective appropriate adjustment in the genetic evaluation model, is required to achieve accurate genetic evaluations for growth. The appropriate adjustment is necessary because the pre-weaning growth potential of a lamb is affected by whether the lamb was born or reared as a singleton or multiple ( Safari et al, 2007 ; David et al, 2011 ; Notter and Brown, 2015 ), and birth type can account for up to 31% of the phenotypic variance in pre-weaning growth ( Hagger, 1998 ). Nonetheless, lambs born into a multiple litter are at greater risk of mortality ( McHugh et al, 2016 ) and, where mortality may have occurred, a reduced litter size may not actually be recorded by the producers.…”
Section: Introductionmentioning
confidence: 99%